PENINGKATAN HASIL BELAJAR GERAK BERIRAMA MELALUI METODE DEMONSTRASI PADA SISWA KELAS VI SDN 1 LANDASAN ULIN SELATAN - Baihaki; Lazuardy Akbar Fauzan; Suadmaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study sought to enhance students' learning outcomes in rhythmic movement via the demonstration method in Physical Education, Sports, and Health (PJOK) for sixth-grade students at SDN 1 Landasan Ulin Selatan. The research context involved students' inadequate proficiency in executing rhythmic motions accurately, a deficiency in self-assurance during practice, and restricted engagement in learning activities. This study utilised Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which comprises the steps of planning, acting, observing, and reflecting. The study involved 21 sixth-grade students, comprising 12 males and 9 females. The research was executed in two phases, each comprising two meetings. Data were gathered by observation and evaluation of rhythmic movement competencies. The findings indicated a substantial enhancement in pupils' academic performance in every cycle. During the pre-cycle phase, the majority of students fell into the sufficient and poor classifications. In Cycle I, the quantity of students in the good and very good categories rose, however in Cycle II, all students attained the good and very good classifications. The demonstration method facilitated students' comprehension of motions by allowing teachers to present direct examples for observation and practice. Consequently, the demonstration method was effective in enhancing rhythmic movement learning outcomes and fostering active, pleasurable, and meaningful PJOK education.